Driving strategic change at the Junior League. (A) - Shumate, Michelle; Howard, Liz Livingston; Waikar, Sachin ([London] : SAGE, 2016)
'Driving Strategic Change at the Junior League' describes a troubled organizational environment. Challenges included a dissatisfied membership, declining membership numbers, a large diversity among local leagues and limited resources to meet the organization's overall objectives. The case describes a 'participatory roadmap' approach, drawing on the insights of comprehensive research, and highlights a strategic-change approach that focuses on participation and local-level flexibility.
Originally Published in: Shumate, M., Livingston Howard, L., & Waikar, S. (2014). Driving Strategic Change at The Junior League (A). 5-413-760(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Association of Junior Leagues; Organizational behavior -- Case studies; Leadership -- Case studies; Nonprofit organizations -- Management -- Case studies